Determinants of Indonesian Real Effective Exchange Rate - Doni Briliant; I Dewa Made Dipta Aditya; Asyib Paqsi Buana (Journal of Research in Business, Economics, and Education, 2020)
As the study of Indonesian Real Effective Exchange Rate is still rare, this research tries to define the determinants of the Indonesian Real Effective Exchange Rate (REER). Variables used in this research are General Fixed Capital Formation (GFCF), Government Final Consumption Expenditure (GFCE), Gross Domestic Product (GDP), Inflation, and the Ratio of Export to Import in the period of 2005 Q1 to 2019 Q4. All of data are obtained from The United States’s Central Bank of The Federal Reserve. Analytical method used in this research is Autoregressive Distributed Lag (ARDL) that is modified with Newey-West HAC Estimator. The results show that in the short run, GFCF and GFCE have no positive effects toward Indonesian REER, yet GDP and the Ratio of Export to Import have positive effects toward Indonesian REER, while Inflation has no a negative effect toward Indonesian REER. In the long run, GFCF, GFCE, and the Ratio of Export to Import have positive effects toward Indonesian REER. GDP has no a positive effect toward Indonesian REER, and Inflation has a negative effect toward Indonesian REER. This research is expected to fill the study gap of Indonesian Real Exchange Rate.